2011
DOI: 10.1177/230949901101900308
|View full text |Cite
|
Sign up to set email alerts
|

Lower Limb Alignment in Anterior Cruciate Ligament–Deficient versus –Intact Knees

Abstract: Small notch width was associated with a thin ACL and can be regarded as an anatomic intrinsic risk factor for ACL injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 37 publications
1
21
2
Order By: Relevance
“…Furthermore, Şenişik et al 26 added that participants had an increased posterior tibial slope in their ACL-injured leg when compared to the contralateral one, and that participants with a posterior tibial slope >9.57° would have a nearly sixfold increased risk of ACL injury. Conversely, Chung et al 22 reported no significant differences on the posterior tibial slope between ACL-deficient and ACL-intact knees.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Furthermore, Şenişik et al 26 added that participants had an increased posterior tibial slope in their ACL-injured leg when compared to the contralateral one, and that participants with a posterior tibial slope >9.57° would have a nearly sixfold increased risk of ACL injury. Conversely, Chung et al 22 reported no significant differences on the posterior tibial slope between ACL-deficient and ACL-intact knees.…”
Section: Resultsmentioning
confidence: 95%
“…Seven studies10 11 14 16 17 20 22 showed that a narrower ICN correlated with a higher risk of ACL injury (table 4). Conversely, Alentorn-Geli et al ,19 Stijak et al 7 and Lombardo et al 18 found no significant difference on ICN width between ACL-injured and non-ACL-injured participants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…slope was associated with ACL tear [5,13,40,43,44,46]; on the contrary, others rejected this correlation [4,8,15,17,18,39,42]. Moreover, there exist two metaanalyses came to totally opposite conclusions [48,49].…”
mentioning
confidence: 99%